Linking immunity and hematopoiesis by bone marrow T cell activity - J.P. Monteiro; A. Bonomo (Brazilian Journal of Medical and Biological Research, 2005)
Two different levels of control for bone marrow hematopoiesis are believed to exist. On the one hand, normal blood cell distribution is believed to be maintained in healthy subjects by an "innate" hematopoietic activity, i.e., a basal intrinsic bone marrow activity. On the other hand, an "adaptive" hematopoietic state develops in response to stress-induced stimulation. This adaptive hematopoiesis targets specific lineage amplification depending on the nature of the stimuli. Unexpectedly, recent data have shown that what we call "normal hematopoiesis" is a stress-induced state maintained by activated bone marrow CD4+ T cells. This T cell population includes a large number of recently stimulated cells in normal mice whose priming requires the presence of the cognate antigens. In the absence of CD4+ T cells or their cognate antigens, hematopoiesis is maintained at low levels. In this review, we summarize current knowledge on T cell biology, which could explain how CD4+ T cells can help hematopoiesis, how they are primed in mice that were not intentionally immunized, and what maintains them activated in the bone marrow.